Usage Behavior of the LINE Application in the Work of Administrative Staff and Its Effects on Characteristics of Records: A Study of the Faculty of Arts, Chulalongkorn University - Tanawuttipong, Kanisorn; Sucha-xaya, Naya (Journal of Information Science Research and Practice, 2025)
Purpose: To examine user behavior and the influence of using LINE application as a tool for work, along with the effects of the application’s use on the characteristics of records. Methodology: The data were collected through a questionnaire administrated to 40 administrative staff members of the Faculty of Arts, Chulalongkorn University. In addition, in-depth interviews were conducted with five staff members, including three administrative staff who completed the questionnaire and two executives from administrative teams. Findings: The findings indicate that administrative staff often use LINE application in their daily work, especially for communication and for sending or receiving records between officers within the same division. The main motivation for this usage is that the application is already used by colleagues, making communication more convenient. However, using LINE affects the characteristics of records, particularly their integrity and usability. Applications of this study: This study can be used as a guideline for improving best practices for LINE application usage at work.